Application of utility-efficient programming to determine economic efficiency of Turkish farmers in the central Anatolian region - Cínemre, Hüseyín Avní; Ceyhan, Vedat (New Zealand journal of crop and horticultural science, 2006)
This research generated stochastically efficient farm plans in the relevant range of risk aversion and calculated the efficiency measures for the three representative farm sizes in the central Anatolian region of Turkey. Utility-efficient programming was used to determine an efficient set of farm plans. Research results showed that total net farm revenue increases for all farm sizes as risk aversion decreases. An economic efficiency score of 0.54 for both small and medium size farms indicated that there is considerable scope for farmers to increase their total net farm revenue using existing technology without additional inputs. Allocative and technical inefficiencies of sampled farms were 0.22 and 0.24, respectively. Thus, supplying complete technical packages for farms may stimulate the adoption of new technologies. Focusing on production practices and marketing efficiency in farmers' training and extension programmes may also help to increase economic efficiency in the research area.